Mobilization of hematopoietic stem cells with the novel CXCR4 antagonist POL6326 (balixafortide) in healthy volunteers—results of a dose escalation trial - Karpova, Darja (J Transl Med, 2017)
BACKGROUND: Certain disadvantages of the standard hematopoietic stem and progenitor cell (HSPC) mobilizing agent G-CSF fuel the quest for alternatives. We herein report results of a Phase I dose escalation trial comparing mobilization with a peptidic CXCR4 antagonist POL6326 (balixafortide) vs. G-CSF. METHODS: Healthy male volunteer donors with a documented average mobilization response to G-CSF received, following ≥6 weeks wash-out, a 1–2 h infusion of 500–2500 µg/kg of balixafortide. Safety, tolerability, pharmacokinetics and pharmacodynamics were assessed. RESULTS: Balixafortide was well tolerated and rated favorably over G-CSF by subjects. At all doses tested balixafortide mobilized HSPC. In the dose range between 1500 and 2500 µg/kg mobilization was similar, reaching 38.2 ± 2.8 CD34 + cells/µL (mean ± SEM). Balixafortide caused mixed leukocytosis in the mid-20 K/µL range. B-lymphocytosis was more pronounced, whereas neutrophilia and monocytosis were markedly less accentuated with balixafortide compared to G-CSF. At the 24 h time point, leukocytes had largely normalized. CONCLUSIONS: Balixafortide is safe, well tolerated, and induces efficient mobilization of HSPCs in healthy male volunteers. Based on experience with current apheresis technology, the observed mobilization at doses ≥1500 µg/kg of balixafortide is predicted to yield in a single apheresis a standard dose of 4× 10E6 CD34+ cells/kg from most individuals donating for an approximately weight-matched recipient. Exploration of alternative dosing regimens may provide even higher mobilization responses. Trial Registration European Medicines Agency (EudraCT-Nr. 2011-003316-23) and clinicaltrials.gov (NCT01841476)